Protocatechuic acid and aldehyde's antioxidant properties are like "new wine in old bottles." - KALYANI, PENDYALA; RAO KODALI, DHANUNJAYA; SRINIVAS, Dr. KUMMARI; PASHA, MOHAMAD JAHANGIR (The journal of contemporary issues in business and government, 2019)
Phenolic compounds are a kind of secondary metabolite found in foods including fruits, vegetables, and spices. Due to their antioxidant, anti-inflammatory, and anti-carcinogenic qualities, they have attracted a lot of interest as a means of protection against a wide range of chronic illnesses. Classed according to their chemical make-up into several categories that include phenolic acids, flavonoids, curcumins, tannins, and antioxidant feature of quinolones..eir structural differences lead to their unique positive benefits on human health. through increasing the production of natural antioxidants, scavenging for free radicals, and generally being all- around good at keeping things from oxidizing too quickly, phenolic chemicals provide protection against oxidative stress. Resistance to apoptosis. 3, 4-dihydroxy benzoic acid, also known as protocatechuic acid (PCA), and protocatechuic aldehyde (PAL; 3,4-dihydroxybenzaldehyde) are polyphenols that grow naturally in produce and plants.